Review on 3-D Printed Drug Delivery Systems - Telrandhe, Moulika .P; Sahithyareddy; Bhargavi V; Nagini T; Nithisha Ch; Sravani .V (Asian Journal of Pharmaceutical Research and Development, 2025)
Pharmaceutical of the field of sciences, 3D printed delivery of drug systems (DDS) arerevolutionizing field. With the using of additive printing techniques, these technologies enable the creation of complex, patient-specific drug delivery devices with specialized geometries, dosage schedules, and controlled release profiles. Since 3D printing may be used to customize drug formulations, dosage forms, and the mixing of many medications into a single device, it is a promising technique for improving therapeutic efficacy and decreasing side effects. This article discusses the application of several 3D printing methods include stereolithography (SLA) and fused deposition modelling (FDM) and selective laser sintering (SLS), in the production of implants, drug-loaded matrices, and devices for targeted or sustained drug release. Furthermore, challenges such as material.